SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU PADA SMKS YASTI CISAAT BERBASIS WEB - Ismawadi, Adi; Naufal Syahrul Anwari, Naufal Syahrul Anwari; Eva Hastuti, Eva Hastuti; Ida Nurlela, Ida Nurlela; Endang Supiani, Endang Supiani; Lis Pahliani Aryani, Lis Pahliani Aryani; Yosal Iriantara, Yosal Iriantara; Supyan Sauri, Supyan Sauri (Wali Pikir: Journal Of Education, 2024)
The development of technology is currently very fast, has penetrated also in the world of education. However, of the majority of schools that have implemented technology in their operations, SMKS YASTI Cisaat is still constrained by the use of technology. New student registration is still done manually. Admission of new students starts from the initial registration of new students, re-registration until the announcement of the results of new student admissions is still manual. This condition is still applied so far, schools often experience errors such as in data input, data processing until the determination of results becomes constrained. The purpose of this study is to be able to provide a website-based design of an information system for new student admissions at SMKS YASTI Cisaat. The urgency of this research if it is not implemented immediately is that it can hinder the development and use of technology at the school level. In addition, there is a risk to keep all vulnerabilities and errors due to manual actions continue to occur. The development model used by the researcher uses the Waterfall Model. In this study, researchers used several stages in the waterfall model, including analysis, design, coding, testing and implementation. The system design uses MySQL as the database as well as PHP and HTML for basic programming. This research succeeded in developing web-based software to assist SMKS YASTI Cisaat in accepting new students.